What does the population in Niger think about a military government? - Daniel Tuki (Democratization, 2024)
Using the Round 9 Afrobarometer survey data for Niger, this study examined the determinants of support for military intervention with particular focus on political instability, perceived corruption in the democratic government, and socioeconomic deprivation. The descriptive results showed that Nigeriens generally do not have a strong aversion towards military rule. In fact, about 70 percent of them agreed that the military should intervene when the democratic government is corrupt. The regression results showed that political instability, which was measured using the total number of violent conflict incidents in the region where respondents resided, was positively correlated with support for military intervention. This might be because people who are exposed to violence feel that a military government would do a better job at providing security. Perceived corruption in government was also positively correlated with support for military intervention. This might be because corruption engenders discontent with democratic institutions, prompting people to see military intervention as a way of curtailing the democratic government's excesses. Socioeconomic deprivation was negatively correlated with support for military intervention, which suggests that the poor prefer democracy to a military government.
https://doi.org/10.7910/DVN/C24ILN
Keywords: D74; I30; 330; military intervention; coup; poverty; political instability; conflict; corruption; Niger